Beyond Content of Conversation: The Role of Conversational Form in the Emergence and Regulation of Social Structure. (February 2017) - Koudenburg, Namkje; Postmes, Tom; Gordijn, Ernestine H.
Social interaction is pivotal to the formation of social relationships and groups. Much is known about the importance of interaction content (e.g., the transfer of information). The present review concentrates on the influence of the act of conversing on the emergence of a sense of solidarity, more or less independently of the content. Micro-characteristics of the conversation (e.g., brief silences, smooth turn-taking) can profoundly influence the emergence and the regulation of relationships and of solidarity. We suggest that this might be because the form of a conversation is experienced as an expression of the social structures within the group. Because of its dynamic nature, moreover, the form of conversation provides group members with a continuous gauge of the group's structural features (e.g., its hierarchy, social norms, and shared reality). Therefore, minor changes in the form and flow of group conversation can have considerable consequences for the regulation of social structure.